Genes and hormones of the hypothalamic–pituitary–adrenal axis in post-traumatic stress disorder. What is their role in symptom expression and treatment response? - Fischer, Susanne; Schumacher, Tabea; Knaevelsrud, Christine; Ehlert, Ulrike; Schumacher, Sarah (Journal of Neural Transmission, 2021)
Background Less than half of all individuals with post-traumatic stress disorder (PTSD) remit spontaneously and a large proportion of those seeking treatment do not respond sufficiently. This suggests that there may be subgroups of individuals who are in need of augmentative or alternative treatments. One of the most frequent pathophysiological findings in PTSD is alterations in the hypothalamic–pituitary–adrenal (HPA) axis, including enhanced negative feedback sensitivity and attenuated peripheral cortisol. Given the role of the HPA axis in cognition, this pattern may contribute to PTSD symptoms and interfere with key processes of standard first-line treatments, such as trauma-focused cognitive behavioural therapy (TF-CBT). Methods This review provides a comprehensive summary of the current state of research regarding the role of HPA axis functioning in PTSD symptoms and treatment. Results Overall, there is preliminary evidence that hypocortisolaemia contributes to symptom manifestation in PTSD; that it predicts non-responses to TF-CBT; and that it is subject to change in parallel with positive treatment trajectories. Moreover, there is evidence that genetic and epigenetic alterations within the genes NR3C1 and FKBP5 are associated with this hypocortisolaemic pattern and that some of these alterations change as symptoms improve over the course of treatment. Conclusions Future research priorities include investigations into the role of the HPA axis in day-to-day symptom variation, the time scale in which biological changes in response to treatment occur, and the effects of sex. Furthermore, before conceiving augmentative or alternative treatments that target the described mechanisms, multilevel studies are warranted.